2019
DOI: 10.1038/s41467-019-08537-y
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans collectively forms dynamical networks

Abstract: Understanding physical rules underlying collective motions requires perturbation of controllable parameters in self-propelled particles. However, controlling parameters in animals is generally not easy, which makes collective behaviours of animals elusive. Here, we report an experimental system in which a conventional model animal, Caenorhabditis elegans, collectively forms dynamical networks of bundle-shaped aggregates. We investigate the dependence of our experimental system on various extrinsic parameters (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(52 citation statements)
references
References 47 publications
(89 reference statements)
0
48
0
2
Order By: Relevance
“…Driven colloidal particles [1][2][3], self-propelled bots [4,5], cells [6,7], animals [8,9], and humans [10] belong to the field of active matter: interacting agents that extract energy from the environment to produce sustained motion or mechanical stresses [3,11,12]. Their collective behavior is fascinating, and the activity and interactions of the individual components give rise to highly nontrivial macroscopic phenomena [13].…”
mentioning
confidence: 99%
“…Driven colloidal particles [1][2][3], self-propelled bots [4,5], cells [6,7], animals [8,9], and humans [10] belong to the field of active matter: interacting agents that extract energy from the environment to produce sustained motion or mechanical stresses [3,11,12]. Their collective behavior is fascinating, and the activity and interactions of the individual components give rise to highly nontrivial macroscopic phenomena [13].…”
mentioning
confidence: 99%
“…In differentiated motile hormogonia of Nostoc punctiforme, Type IV pili are identified as the means of motility [42]. In this case, molecular analysis has revealed that the Type IV-pilus-like structure is encoded by pil and hps genes that play roles in motility and polysaccharide secretion [46,47,48]. According to Khayatan et al [45], the pil and hps genes are reportedly conserved in Pseudanabaena sp.…”
Section: Bundles and Single Filamentsmentioning
confidence: 99%
“…We employed an agent-based model to reproduce scattered clusters on solid media. The model is based on a recently proposed model reproducing the collective pattern formations in C. elegans [46], which itself is derived from a model for the pattern of large vortices of microtubes in vitro [50,51]. The key features of this model are identified as follows: (i) the direction of movement of each particle attains uniformity by nematic order; and (ii) the rotation rate of particles is maintained for a relatively long period, as we have observed in Pseudanabaena.…”
Section: Mathematical Modeling Of the Scattered Patternmentioning
confidence: 99%
See 1 more Smart Citation
“…appx 5 and SI, Appendix section 12-5) 19,20,25,73,74 . Animal and human behaviors can also be modeled as active matter governed by attractive and repulsive interactions [75][76][77][78] .…”
Section: Profile Of Effective Potentials Of Cell-cell Interactionmentioning
confidence: 99%